Coronation of Her Majesty Queen Elizabeth II – Programme of Events (Colonial Letters and the Contact of Knowledges, 1953)
This file contains colonial letters on coronation of Queen Elizabeth II
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies